On-the-Job Ethics - Proximity Morality Forming in Medical School - Hans O. Thulesius (Grounded Theory Review: An International Journal, 2009)
On-the-job-ethics exist in all businesses and can also be called proximity morality forming. In this paper we propose that medical students take a proximity morality stance towards ethics education at medical school. This means that they want to form physician morality “on the job” instead of being taught ethics like any other subject. On-the-job-ethics for medical students involves learning ethics that is used when practicing ethics. Learning ethics includes comprehensive ethics courses in which quality lectures provide ethics grammar useful for the ethics practicing in attitude exercises and vignette reflections in tutored group discussions. On-the-job-ethics develops professional identity, handles diversity of religious and existential worldviews, trains students described as ethically naive, processes difficult clinical experiences, and desists negative role modeling from physicians in clinical or teaching situations. This grounded theory analysis was made from a questionnaire survey on attitudes to ethics education with 409 Swedish medical students participating. We analyzed over 8000 words of open-ended responses and multiple choice questions using classic grounded theory procedures, but also compared questionnaire data using statistics such as multiple regression models. The paper gives an example of how grounded theory can be used with a limited amount of survey data.